Acute partial sleep restriction attenuates working memory performance and does not affect BDNF in young adults - Cherubini Joshua M.; Walker David; So Jared; Nguyen Luke; MacDonald Maureen J.; Walsh Jeremy J. (Translational Exercise Biomedicine)
Sleep loss decreases working memory (WM) performance in young adults. The mechanisms that regulate WM performance during sleep loss are integrative and likely depend on the duration of perturbed sleep. The aim of this research was to investigate the impact of a single night of partial sleep restriction (PSR) on WM, and the extent to which factors such as cardiorespiratory fitness and brain-derived neurotrophic factor (BDNF) influence WM performance following one night of PSR.